Dexmedetomidine and S(+)-ketamine in ischemia and reperfusion injury in the rat kidney - Curtis,Fabio Geraldo (2011)
PURPOSE: To investigate blood creatinine and renal histology in rats anesthetized with S(+)-ketamine (keta) or dexmedetomidine (dex) and submitted to kidney ischemia/reperfusion injury (IRI). METHODS: Under intraperitoneal (ip) S(+)-ketamine, 20 male Wistar rats were divided into two groups (n=10): maintenance with iv S(+)-ketamine or dex (keta and dex groups), and submitted to right (R) nephrectomy and left (L) renal artery clamping for 45 min. Blood creatinine was measured before ischemia (T1) and 48h after reperfusion (T2), when L nephrectomy was performed. Histological analysis was performed in all kidneys. RESULTS: Blood creatinine was significantly higher at T2 in both groups, but dex group results were lower than those of keta group. Histological changes: between groups, R kidneys did not differ; there were significant high scores for vascular dilation: keta L kidneys; for vascular congestion, tubular dilation, and necrosis: L kidneys from both groups; for tubular degeneration: keta R kidneys. CONCLUSION: S(+)-ketamine plus IRI were aggressive to rat kidneys, according to histological changes, and dexmedetomidine may have not totally protected the kidneys from these injuries, despite the better results of blood creatinine.